Implementation of The Daily Mile™: survey of primary schools in Greater London. (20th October 2021) - Ram, B; Chalkley, A; van Sluijs, E; Hargreaves, D; Viner, R; Saxena, S
Abstract: Background: The Daily Mile™ is a free school-based active mile intervention. Its main features include that children run or jog for 15 minutes at least 3 times a week (3x/wk) during school hours. The Daily Mile Foundation recommends 10 principles for successful implementation. These are it is (1) quick (15 minutes), (2) fun, (3) whole school participates, (4) it takes place in all weathers, (5) 3x/wk in addition to curricular lessons (not during PE, breaks, before/after school), (6) ideally in the school playground, (7) safe, (8) simple (no equipment), (9) children go at their own pace and (10) no change of clothes or shoes is needed. The aim of this study was to identify how many Greater London primary schools adopting The Daily Mile implement its 10 principles. Methods: In September 2020, we sent all state-funded primary schools (n = 1721) in every Greater London borough (n = 32) a survey to find out if and how they implemented The Daily Mile. Results: By June 2021, 368 (21%) schools responded to our survey (at least one from every London borough). Of these, 195 (53%) schools adopted The Daily Mile of which only 7 (4%) reported implementing all 10 principles; a median 7 (IQR: 6, 8) principles were reported implemented. Whole school participation was reported by 93 (48%) Daily Mile schools, 104 (53%) reported implementing The Daily Mile for 15 minutes, 127 (65%) implemented it at least 3x/wk, and 149 (76%) schools reported that the children ran or jogged during The Daily Mile. A large proportion of schools reported implementing The Daily Mile in the school playground and that it was done simply (both n = 171, 88%), but only 85 (44%) schools reported implementing it during lessons. Conclusions: Daily Mile schools in Greater London implement 7/10 principles on average. Whether implementing all the principles limits the success of its desired effect is unclear. Studies assessing effects of The Daily Mile should consider its implementation when reporting results. Key messages: Of The Daily Mile's 10 principles, an average of 7 are implemented in London schools. Studies examining The Daily Mile should consider implementation which may impact its desired effect.